STUDY OF CANNABINOIDS CONTENT IN MARIHUANA SAMPLES ( Cannabis sativa L.)CULTIVATED IN SEVERAL REGIONS OF COLOMBIA - FLORIAN R., Néstor M.; PARADA A., Fabián; GARZÓN M., William F. (Vitae, 2009)
The present study analyzes the cannabinoids content in samples of Cannabis sativa L. cultivated illicitly in Colombia. The physicochemical conditions are optimized for the extraction and quantification of Cannabidiol (CBD), 9-Tetrahidrocannabinol (THC) and Cannabinol (CBN) starting from a vegetable sample using gas chromatography with flame ionization detector (GC-FID), validating the respective analytic method. Samples coming from four diferent Colombian regions are analyzed (Llanos Orientales, LL; Cauca, CA; Sierra Nevada de Santa Marta, SN; Eje Cafetero, EC). The study let determination of CBD, THC and CBN samples quantitatively. The average content of THC in the samples of the region LL is of 15.74% ± 2.92, in the region CA is of 10.98% ± 6.70, in the region SN is of 2.81% ± 1.72 and in the region EC of 1.87 % ± 1.25. The higher content of THC in vegetable samples of Cannabis from the Llanos Orientales (LL) and Cauca (CA) could be indicative of the employment of improved varieties. This fact generates a great concern about the potential effects produced by the drug in consumers.